تأثير الوصلات اللحامية على التشقق الهيدروجيني لأنابيب وحدة الأمين في شركة مصفاة بانياس - سلامة, أحمد; بركات, نيرودا; حسن, رانيه (Latakia University Journal -Engineering Sciences Series, 2019)
In this research, we study had the effect of weldment joints on hydrogen-induced carking (HIC) in amine transport pipelines where we have simulated the welding process of two types of pipes :the first one is A106GRB (which is used in the amine unit) which have real dimensions by using SolidWorks 2014 SP3, the second one is A335 P5 (a pipe type, which we suggest it as an alternative metal) which also have dimensions similar to the last one, the results of thermal comparison between the two types of steel indicated that the thermal gradient in the heat affected zone in A106GRB is greater than A335P5 . In order to study phase transformations in the heat affected zone, we have modeled these transformations by using JMat Pro 7 according to thermal gradient results from the previous study on both: A106GRB and A335 P5, the aim of this study is to know the structures and phases resulting from welding in each thermal field in the heat affected zone. تأثير الوصلات اللحامية على التشقق الهيدروجيني لأنابيب وحدة الأمين في شركة مصفاة بانياس في هذا البحث تم دراسة تأثير الوصلات اللحامية على التشقق الهيدروجيني، لأنابيب وحدة الأمين، حيث تمت نمذجة عملية اللحام لأنبوبين من النوع A106GRB (وهو النوع المستخدم في وحدة الأمين في المصفاة) بأبعادهما الحقيقية باستخدام برنامج SolidWorks 2014 SP3، ومن ثم كررت النمذجة لأنبوبين ملحومين من النوع A335 P5(وهو نوع الأنابيب الذي نقترح استبدال الأنابيب السابقة به)، وبنفس أبعاد الأنابيب السابقة، حيث أشارت نتائج المقارنة الحرارية بين نوعي الفولاذ أن التدرج الحراري لمنطقة التأثر الحراري في الفولاذ من النوع A106GRB يكون أكبر منه في الفولاذ A335 P5 . ومن أجل دراسة التحولات الطورية في منطقة التأثر الحراري قمنا نمذجة هذه التحولات وفقاً للتدرج الحراري الناتج عن الدراسة السابقة باستخدام برنامج JMatPro7، وذلك لكلا نوعي الفولاذ المذكورين ، بهدف معرفة البنى والأطوار الناتجة عن اللحام لكل مجال حراري في منطقة التأثر الحراري وإغناء البحث في هذا المجال.